Is it morally permissible for women in their third trimester to withdraw consent of pregnancy when carrying a child with disabilities - Lim, Jade Si Min (Nanyang Technological University, 2023)
This paper argues for the moral permissibility of women in their third trimester to withdraw consent of pregnancy when carrying a child with disabilities. It emphasizes the importance of bodily autonomy and sustained consent, and raises possible arguments against the stance of withdrawing consent of pregnancy when carrying a child with disabilities, which includes ableism, stigmatization, autonomy, human dignity, and social justice. The proposal made to support the moral permissibility of withdrawing consent of pregnancy when carrying a child with disabilities is due to several reasons such as the challenges in changing societal attitudes, the dependence that people with disabilities have on caregivers, the value of life in terms of their contribution to society, more harm done on both mother and foetus if she was forced to carry on with the pregnancy to full-term and lastly, the possibility of false negative results which leads to the woman’s inability to withdraw consent of pregnancy earlier. Ultimately, it is concluded that it is morally permissible for women in their third trimester to withdraw consent of pregnancy when carrying a child with disabilities up to week 33 due to the foetus's incomplete brain development.